UPAYA MENINGKATKAN KOMPETENSI MENGGAMBAR AUTOCAD DENGAN METODE PEER TUTORING DI KELAS XI DPIB A DI SMK NEGERI 1 PAJANGAN BANTUL - Andrianto Hari Wibowo (INCARE, International Journal of Educational Resources, 2021)
This classroom action research is motivated by the not yet maximal competence of students in drawing using the AutoCAD program in the subjects of Software Applications and Building Interior Design. This study has the following objectives: 1) to determine the learning process of students to draw AutoCAD in the subject of Software Applications and Building Interior Design using the Peer Tutoring learning model, 2) to determine student learning achievement in terms of psychomotor and affective abilities of class XI DPIB students. A draws AutoCAD in Software Applications and Building Interior Design subjects during the lesson. This study was conducted from July to November 2019 at SMK Negeri 1 Pajangan. The subject of this research is class XI DPIB A as many as 28 students. This classroom action research procedure uses 2 cycles, each cycle consisting of 2 meetings. Each cycle consists of planning, implementation, observation, reflection. Data collection uses an assessment sheet that is compiled based on the student product assessment criteria. The indicator of the success of this research is an increase in student learning outcomes, namely at least the students are complete. The results showed that the use of the Peer Tutoring learning model could improve students' AutoCAD drawing competence in Software Applications and Building Interior Design subjects. In the first cycle of students who are 75% competent and the second cycle of students who are 100% competent.